Comparison of dissolved gases in natural ester under partial discharges - Jongvilaikasem, Korraya; Maneerot, Sakda; Jariyanurat, Kittipod; Pattanadech, Norasage (My University, 2019)
Currently, natural ester is alternative liquid insulation applied for both distribution and power transformers. Generally, transformers are expected to operate stably and reliably. However, their functions may fail during operation. Dissolved gases analysis is one of the worldwide accepted diagnostic techniques to examine the insulation integrity of the transformers. This paper presents the analysis of dissolved gases generated from partial discharge (PD) experiments i.e. corona discharge, surface discharge and internal discharge which were conducted in the test cell filled with natural ester (FR3). To simulate corona discharge, a needle electrode with a tip radius of 10, 20, and 40 micrometers was used as high voltage electrode and the plane electrode with a diameter of 45 mm was used as a grounded electrode. The gap distance was fixed at 32 mm. The corona discharge experiment was performed for 2 hours at the test voltage level of 35, 40, 45 kV respectively. In case of surface discharge, the pressboard samples i.e. non-impregnated pressboards, 8-hour impregnated pressboards, and 16-hour impregnated pressboards were inserted between the 20-micrometer tip radius needle and grounded plane. Then, the test voltage of 25 kV was applied to the electrode system for 1 hour. Besides, the surface discharge was tested at 35 and 45 kV respectively. For internal discharge, the pressboard samples i.e. non-impregnated pressboards, 8-hour impregnated pressboards, and 16-hour impregnated pressboards were inserted between the plane-plane electrodes. Then the test voltage of 25 kV was applied to the electrode system for 1 hour. Moreover, the internal discharge was tested also at 35 and 45 kV. Their natural ester samples were sampling from the test cell for each experiment and the dissolved gases were measured and analyzed. From the test results, it was found that the types and quantity of dissolved gases depended strongly on the type of discharge and material samples.
Keywords: Corona discharge; Dissolved gases analysis; Internal discharge; Natural ester; Surface discharge; Transformer